IMPROVING THE ACCOUNTING OF COMMODITY-MATERIAL RESERVES IN COMMERCIAL BANKS (International conference on multidisciplinary science, 2025)
Internal audit is a cornerstone of transparency, accountability, and efficiency in managing public funds, particularly within budgetary operations. This article explores the effective organization of internal audits in the budget framework, focusing on key principles such as independence, risk-based approaches, and adherence to international standards. It highlights essential components, including audit charters, skilled teams, advanced tools, and stakeholder engagement, that enhance the credibility and impact of internal audits. The article also examines common challenges, such as resource constraints, resistance to change, and technological limitations, while proposing strategies to overcome these obstacles, including the adoption of advanced technologies and fostering a culture of accountability. By implementing robust internal audit systems, organizations can ensure compliance, optimize resource utilization, and promote trust and transparency, ultimately strengthening governance and financial performance in the management of public budgets.